Renewable energy in sustainable cities: Challenges and opportunities by the case study of Nusantara Capital City (IKN) - Yudiartono, Yudiartono; Santosa, Joko; Fitriana, Ira; Wijaya, Prima Trie; Rahardjo, Irawan; Abdul Wahid, La Ode Muhammad; Siregar, Erwin; Hesty, Nurry Widya; Fithri, Silvy Rahmah; Sugiyono, Agus (Center of Biomass & Renewable Energy (CBIORE), 2024)
This study explores strategies for optimizing energy consumption in Indonesia's New Capital City (IKN) to achieve net zero emissions by 2045, focusing on energy efficiency, sustainable mobility, and renewable energy through the Low Emissions Analysis Platform (LEAP) model. Sustainable cars, such as renewable-energy-powered electric and green hydrogen-powered vehicles, can reduce energy consumption by 43% in 2045 and 33% in 2060, respectively, compared to BAU. GHG emissions per capita will drop 70% in 2045 and 63% in 2060. In NZE scenario, IKN can reach 100% green energy by 2045 with a 4.4 GW solar power plant, a 0.92 GWh BESS, and a full load hour capability of 4 hours. By 2045, 1.1 GW of hydropower and 143 MW of wind power are expected to be utilized. In 2060, hydropower will be 2.8 GW, wind power will be 184 MW, and solar power will be 8 GW with 1.6 GWh of BESS. Lack of legislation, technical expertise, high prices, inadequate grid infrastructure, and renewables shortfalls restrict Indonesia's BESS. Solar installation criteria, subsidies, and off-grid project incentives can all help ease BESS use. Forecasts predict 0.53 GW of rooftop solar PV capacity by 2045 and 3.35 GW by 2060. Net metering and solar tariffs boost rooftop solar system profitability. One ton of green hydrogen production requires 55.7 MWh from a solar power plant. Solar power plant capacity will rise to 0.49 GW by 2045, producing 19,359 tons of green hydrogen, and almost quintuple to 89,594 tons by 2060. Hydrogen generation, storage, transit, and distribution require specific infrastructure due to high capital costs and a lack of networks, yet interest in them is growing.